The act of living : Street Life, Marginality, and Development in Urban Ethiopia. - Di Nunzio, Marco (Cornell University Press, 2019)
The Act of Living explores the relation between development and marginality in Ethiopia, one of the fastest growing economies in Africa. Replete with richly depicted characters and multi-layered narratives on history, everyday life and visions of the future, Marco Di Nunzio's ethnography of hustling and street life is an investigation of what is to live, hope and act in the face of the failing promises of development and change. Di Nunzio follows the life trajectories of two men, "Haile" and "Ibrahim," as they grow up in the Ethiopian capital Addis Ababa, enter street life to get by, and turn to the city's expanding economies of work and entrepreneurship to search for a better life. Apparently favourable circumstances of development have not helped them achieve social improvement. As their condition of marginality endures, the two men embark in restless attempts to transform living into a site for hope and possibility. By narrating Haile and Ibrahim's lives, The Act of Living explores how and why development continues to fail the poor, how marginality is understood and acted upon in a time of promise, and why poor people's claims for open-endedness can lead to better and more just alternative futures. Tying together anthropology, African studies, political science, and urban studies, Di Nunzio takes readers on a bold exploration of the meaning of existence, hope, marginality, and street life. -- Présentation de l'éditeur.